The Effect of Sea Sand Mining on Fishermen's Rights - Rizkal Nur; Andi Kurniawati; Thiodores, Dyno (Faculty of Law, Mulawarman University, 2021)
Sea sand mining has a significant impact on fishermen who have fishing areas in Spermonde Waters. The purpose of this study is to see the impact of sea sand mining on the rights of fishermen who daily catch fish around the Spermonde Waters which are the location of sand mining. This research method is a qualitative method using data collection techniques in the form of, (1) literature review, to examine related policies; (2) Interview, to get related information; and (3) observation. The result of the research is that there are changes in the marine environment ecosystem due to this mining. The dredging of sea sand causes the sea water to become cloudy, resulting in reduced fish catches in the area. The occurrence of economic degradation of the community, especially fishermen, before and after mining occurs so that it violates the rights of fishermen that have been mandated in the law.